Energy-Based Methods and Nanocarrier-Based Approaches for Melasma Treatment - Amiremad Kheirieh; Amirhessam Kheirieh; Zahra Mahdavi; Ali Mohammad Halvani; Amir Mohammad Bagheri; Hooriyeh Nassirli; Shiva Golmohammadzadeh; Bizhan Malaekeh-Nikouei (Advanced Pharmaceutical Bulletin)
Purpose: Melasma is a persistent skin condition caused by excessive melanin production, particularly affecting women’s quality of life. It can result from various factors like sun exposure, genetics, hormones, medications, or inflammation. Effective melasma treatment requires products that can deeply penetrate the skin. The outermost skin layer, known as the stratum corneum (SC), plays a crucial role in delivering topical and transdermal drugs. Researchers have developed numerous strategies to enhance skin permeability and drug efficacy. Methods: This review delves into energy-based techniques and nanocarrier systems for treating melasma, specifically focusing on improving drug delivery to the viable epidermis (EP) while overcoming the SC barrier. Results: Physical methods offer benefits such as enhanced skin penetration but come with drawbacks like frequent visits, high costs, and the need for specialized equipment and skilled operators. Microneedle patches are gaining attention as a convenient physical treatment option for delivering multiple medications effectively, offering targeted delivery and minimal side effects. Nanocarrier systems like transferosomes demonstrate promise in enhancing skin penetration for treating melasma and skin hyperpigmentation. While they offer advantages such as high drug entrapment and improved bioavailability, challenges like stability issues and scalability hinder their widespread adoption. Conclusion: Energy-based techniques enhance drug penetration but can lead to scarring and burns, while dissolvable micro-needles offer a convenient and effective alternative. Nano-drug carriers, like nanostructured lipid carriers (NLCs) and transferosomes, show promise for improved skin drug delivery with their flexible structures and enhanced penetration capabilities, yet further clinical research is needed for definitive conclusions